The Correlation of Interpersonal Communication among the Elderly and its Impact on Family Harmony - Aneng Yuningsih (Genius Journal, 2023)
Introduction: Declining physical condition in the elderly, reduced income, limited relationships threaten the self-existence and happiness of the elderly. Technological developments make the world rush (hurried world), and result in the elderly being left behind, marginalized, alone, lonely, unhappy and sickly, which will eventually burden families and the country. The external challenge faced by the elderly today is the rapid development of technology. The elderly, in their old age, have to deal with an environment that is different from the environment in which they were raised. The limitations of elderly interpersonal communication with family harmony today will certainly be a challenge in maintaining harmony in the family. Objective: The purpose of this study was to determine elderly interpersonal communication with family harmony in the globalization era. Method: This type of research is quantitative, with a cross sectional approach. Total population of 112 elderly with a sample of 53 samples selected using a purposive sampling approach. Statistical data processing using the SPSS for windows application. Bivariate analysis used the Chi Square statistical test with an alpha of 0.05. Result: The results of the study can be concluded that there is a relationship between elderly interpersonal communication and family harmony as indicated by the P Value of 0.000. Conclusion: The advice that can be given is to increase the intensity of family meetings with the elderly to establish more intimate interpersonal relationships so that they can have a better effect on the elderly in the current era of globalization